COUPLED-CHANNEL CALCULATIONS ON ROVIBRATIONAL EXCITATION OF H2O IN COLLISIONS WITH H-ATOMS - Bissonnette, C; Clary, D (1993)
Coupled channel calculations are used to obtain state-to-state scattering cross sections for non-reactive H + H2O collisions. Cross sections are calculated at energies for which collisionally induced vibrational and rotational transitions in H2O are possible. The results of the calculations show that excitation of the asymmetric stretch vibration υ3 = 1 of H2O is accompanied by excitation of in-plane H2O rotations. This observation compares favourably with results obtained in a recent experimental study and with recent quasiclassical calculations. © 1993.